1971
DOI: 10.1302/0301-620x.53b4.718
|View full text |Cite
|
Sign up to set email alerts
|

Compression of the Deep Palmar Branch of the Ulnar Nerve by an Anomalous Muscle

Abstract: 1. A case of compression of the deep palmar branch of the ulnar nerve by an accessory abductor minimi digiti muscle is described. 2. The morphology of abnormal muscles in the hypothenar region is discussed. 3. Five previously reported cases of ulnar nerve compression at the wrist by an anomalous muscle are reviewed. 4. When symptoms are produced by an anomalous hypothenar muscle, they seem to be related to the anatomical site of the muscle and the presence of muscle hypertrophy. Occupational factors may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 15 publications
1
46
0
1
Order By: Relevance
“…Roberts (1972) and Lahey and Aulicino (1986) identify anomalous muscles originating from PL acting as accessory muscles of abduction and flexion of the fifth digit, while Still and Kleinert (1973) describe an aberrant PL muscle passing through Guyon's canal. An anomalous muscle in the lower forearm in the absence of PL was referred to by Jeffery (1971) as accessory abductor minimi digiti. However, none of these muscles displayed attachments corresponding to the muscle described here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Roberts (1972) and Lahey and Aulicino (1986) identify anomalous muscles originating from PL acting as accessory muscles of abduction and flexion of the fifth digit, while Still and Kleinert (1973) describe an aberrant PL muscle passing through Guyon's canal. An anomalous muscle in the lower forearm in the absence of PL was referred to by Jeffery (1971) as accessory abductor minimi digiti. However, none of these muscles displayed attachments corresponding to the muscle described here.…”
Section: Discussionmentioning
confidence: 99%
“…Compression of the ulnar nerve by this muscle can occur within Guyon's canal. Although ulnar nerve compression at the level of the wrist by anomalous muscles is rare (James et al, 1987;Sheppard et al, 1991), it is not uncommon, as several cases have been reported (Jeffery, 1971;Still and Kleinert, 1973;Sälgeback, 1977;Lahey and Aulicino, 1986;James et al, 1987). It has also been suggested that ulnar artery thrombosis may be associated with an anomalous muscle in Guyon's canal (Pribyl and Moneim, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous descriptions a similar accessory ADM muscle beam was reported to originate from palmaris longus and the palmar aponeurosis (Wood, 1867;Soldado-Carrera et al, 2000), from the flexor carpi radialis tendon (Bakinde et al, 2005), from the flexor carpi ulnaris tendon (Hill et al, 2006), from the transverse carpal ligament (Netscher and Cohen, 1997), solely from the deep antebrachial fascia (Jeffery, 1971;Salgeback, 1977;Turner and Caird, 1977) or both from the flexor retinaculum and deep antebrachial fascia (Sheppard et al, 1991;Sanudo et al, 1993;Netscher and Cohen, 1997;Vollala et al, 2005). In the present case the additional ADM took origin from the deep antebrachial fascia and the tendon of FDS muscle to the middle finger.…”
mentioning
confidence: 87%